2004
DOI: 10.1007/s00384-004-0639-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the intestinal mucosa of patients with inflammatory bowel disease: evidence of altered expression of FasL and perforin cytotoxic pathways

Abstract: Increased expression of FasL in IBD colonic LP not parallelled by Fas on T-cells and macrophages may indicate a reduced susceptibility to the Fas/FasL-mediated apoptosis of lymphoid cells. Expression of perforin is correlated to the tissue damage, and may represent the enhancement of a distinct cytotoxic pathway in UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 31 publications
1
69
1
Order By: Relevance
“…32,33 Furthermore, the expression of perforin has been correlated with tissue damage in active disease. 34 Consistently, reduced chronic inflammation was noted in perforin-deficient mice in our experiments, indicating an involvement of the perforin pathway in controlling the activity of chronic colitis in the AOM/DSS model. This concept is also underlined by studies by Souza et al, 34 who found that deficiency in perforin but not FasL resulted in reduced activity of colitis in an adoptive transfer model in which bone marrow cells were used to reconstitute Tg26 mice.…”
Section: Discussionsupporting
confidence: 79%
“…32,33 Furthermore, the expression of perforin has been correlated with tissue damage in active disease. 34 Consistently, reduced chronic inflammation was noted in perforin-deficient mice in our experiments, indicating an involvement of the perforin pathway in controlling the activity of chronic colitis in the AOM/DSS model. This concept is also underlined by studies by Souza et al, 34 who found that deficiency in perforin but not FasL resulted in reduced activity of colitis in an adoptive transfer model in which bone marrow cells were used to reconstitute Tg26 mice.…”
Section: Discussionsupporting
confidence: 79%
“…Although the etiology of IBDs remains unclear, a sustained overproduction of proinflammatory cytokines and excessive cell death coupled with the impaired clearance of apoptotic cells (ACs) in the intestinal lamina propria have been implicated as the primary reasons for failure to resolve acute inflammation in the gut (3). High levels of apoptosis have been observed in the intestinal epithelium of ulcerative colitis patients (4)(5)(6). Moreover, several animal studies confirm the role of apoptosis in IBD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, reduced apoptotic responses in colonic epithelial CaCo-2 cells improve viability and transmembrane resistance (17). Apoptosis is also evident in the colonic mucosa of patients with inflammatory bowel disease (IBD) (18), and in the DSS model of colitis (19). Akt, or protein kinase B, plays a critical role in controlling the balance of survival and apoptosis (20,21).…”
mentioning
confidence: 99%